2009
DOI: 10.1073/pnas.0812625106
|View full text |Cite
|
Sign up to set email alerts
|

Integration of evolutionary and desolvation energy analysis identifies functional sites in a plant immunity protein

Abstract: Plant immune responses often depend on leucine-rich repeat receptors that recognize microbe-associated molecular patterns or pathogen-specific virulence proteins, either directly or indirectly. When the recognition is direct, a molecular arms race takes place where plant receptors continually and rapidly evolve in response to virulence factor evolution. A useful model system to study ligand-receptor coevolution dynamics at the protein level is represented by the interaction between pathogen-derived polygalactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
80
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 53 publications
(117 reference statements)
5
80
0
Order By: Relevance
“…Remarkably, many residues that were previously selected and validated as hot spots for this interaction (Casasoli et al, 2009) were found at the protein-protein interface of the complex (see "Discussion"). The active site of FpPG is located in a deep cleft that is open on both sides to allow the accommodation of the substrate (homogalacturonan) and the release of the hydrolysis products.…”
Section: Structure-assisted Design Of Pvpgip2 Site-directed Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, many residues that were previously selected and validated as hot spots for this interaction (Casasoli et al, 2009) were found at the protein-protein interface of the complex (see "Discussion"). The active site of FpPG is located in a deep cleft that is open on both sides to allow the accommodation of the substrate (homogalacturonan) and the release of the hydrolysis products.…”
Section: Structure-assisted Design Of Pvpgip2 Site-directed Mutantsmentioning
confidence: 99%
“…Genes encoding PGIPs are under selective pressure for diversification and a number of hot spots for the interaction with PGs have been identified on the inhibitor concave surface and validated by site-directed mutagenesis (Casasoli et al, 2009). Unlike for other CWDE inhibitors that engage many contacts in the interaction with their partners (Payan et al, 2004;Raiola et al, 2004;Di Matteo et al, 2005), only a few residues, sometimes only one, are critical for maintaining the stability of the PG-PGIP interaction (Leckie et al, 1999;Casasoli et al, 2009). This is probably why, despite the efforts made during the past years, the crystal structure of the complex is not available yet.…”
mentioning
confidence: 99%
“…This is due to the bridging by Ca ++ of antiparallel HGA chains with continuous runs of dissociated and negatively charged carboxyl groups to form structures called "egg-boxes" (4-6). Fragments of HGA, named oligogalacturonides (OGs), function as danger signals and induce the expression of defense genes and proteins (5,(7)(8)(9)(10), protecting plants against fungal diseases (11). Besides inducing defense responses, OGs also affect several aspects of plant growth and development (5,12).…”
mentioning
confidence: 99%
“…Well-characterized DAMPs are the oligogalacturonides (OGs), pectin fragments released from the plant cell wall by fungal polygalacturonases (Hahn et al, 1981;Ridley et al, 2001). The accumulation of active OGs, with a degree of polymerization between 10 and 15, is favored by the presence of polygalacturonase-inhibiting proteins in the apoplast (De Lorenzo and Ferrari, 2002;Casasoli et al, 2009). OGs elicit a variety of responses, including the production of reactive oxygen species (ROS; Bellincampi et al, 2000;Galletti et al, 2008), a rapid modification of membrane polarization and ion fluxes (Mathieu et al, 1991;Thain et al, 1995), the induction of defense-related genes, and the accumulation of phytoalexins (Davis et al, 1986).…”
mentioning
confidence: 99%